2020
DOI: 10.1016/j.bbi.2019.04.041
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle and biological factors influence the relationship between mental health and low-grade inflammation

Abstract: Mental health modulates the risk of common chronic conditions like cardiovascular disease, cancer and diabetes. Although inflammation is thought to partly explain this link, its relation with mental health is still unclear and largely unexplored.We investigated three scales assessing psychological resilience (CD-RISC), depression symptoms (PHQ8) and mental wellbeing (SF36-MCS) in an Italian adult population cohort (N max =16,952). We performed stepwise generalized linear models to test the association between … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 86 publications
5
31
1
Order By: Relevance
“…This association was quite robust across varying p-value thresholds (P T ranging from 0.001 to 1.0; Figure 1). Overall, the evidence reported here suggests PDW as a new potential biomarker for Parkinson's disease and is consistent with previous studies reporting positive associations between PDW and depression risk and/or symptoms, both at the epidemiological level (17,24) and at the genetic level (16). Indeed, depression represents one of the main non-motor symptoms of PD, often presenting in its prodromal phase (25), and shows progressive patterns of microglial activation like other neurodegenerative disorders (26).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This association was quite robust across varying p-value thresholds (P T ranging from 0.001 to 1.0; Figure 1). Overall, the evidence reported here suggests PDW as a new potential biomarker for Parkinson's disease and is consistent with previous studies reporting positive associations between PDW and depression risk and/or symptoms, both at the epidemiological level (17,24) and at the genetic level (16). Indeed, depression represents one of the main non-motor symptoms of PD, often presenting in its prodromal phase (25), and shows progressive patterns of microglial activation like other neurodegenerative disorders (26).…”
Section: Resultssupporting
confidence: 91%
“…They reported non-significant genetic correlations with both Plt and MPV in the largest PD case-control GWAS metaanalysis carried out so far (involving ∼ 56,300 PD cases and ∼ 1.4 million controls) (15). Of note, in spite of the previous implication of PDW in neurodegenerative disorders (4,(9)(10)(11) and, more recently, in comorbid disorders like major depression (16,17), this parameter has never been investigated with reference to PD risk at the genetic level.…”
Section: Introductionmentioning
confidence: 99%
“…However, they were notably weakened by adjustment for obesity, in line with previous evidence that body mass index (BMI) attenuates the association between systemic inflammation and somatic depressive symptoms (Case & Stewart, 2014;Chamberlain et al, 2019;Duivis et al, 2013;Krogh et al, 2014;White et al, 2017), in particular appetite (Lamers et al, 2018). For this symptom, the link with fat mass may be particularly complex, in view of the likely bidirectional relationship between depressive symptoms and systemic inflammation (Gialluisi et al, 2019). In this context, the fat mass may act (a) as a confounder of the relationship, influencing independently circulating inflammation and appetite; (b) as a mediator of the effect of appetite on inflammation; or (c) as an ancestral exposure influencing inflammation and, in turn, appetite, or vice versa (explained in Figure 2).…”
Section: Discussionsupporting
confidence: 80%
“…Then we repeated the logistic model for the four component biomarkers of INFLA-score, namely Plt, CRP, WBC, and GLR. In this case, a further correction for four independent markers tested was applied (α = 2.1 × 10 −3 ), since MatSpD did not detect any reduction in the number of latent variables (Gialluisi et al, 2019).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…It has been reported that mental disorders, especially depression and anxiety disorders, could affect the in ammation level [16], cytokines [17] and chemokines [18], neurotransmitter metabolism [19,20], neuroendocrine function [21], and so forth, which are also recognized as possible causes for the development and heterogeneity of GBM [22]. And research have also discovered that compared with other form of cancers, glioblastoma could be concomitant with depression/anxiety [23,24].…”
mentioning
confidence: 99%